Knowledge management system application in distance education - Belevičiūtė, Inga; Kulvietis, Genadijus (Lietuvos matematikos rinkinys, 2004)
Society is entering an era the future essentially will be determined by people's ability to wisely use knowledge. This paper presents how knowledge management can be used in distance education.
Keywords: knowledge system; knowledge management; distance education